Lymphoepithelioma-like carcinoma of the endometrium: Case report of a rare tumour with comprehensive immunohistochemical and molecular analysis - Němejcová, Kristýna; Hájková, Nikola; Tichá, Ivana; Bártů, Michaela; Dolínská, Dagmar; Kalist, Vladimír; Dundr, Pavel (Polish Journal of Pathology, 2018)
We are reporting a case of endometrial lymphoepithelioma-like carcinoma (LELC) in a 63-year-old female. Microscopically, the tumor consisted of groups of tumor cells surrounded by dense lymphoplasmacytic infiltrate. Immunohistochemically, the tumour cells were positive for cytokeratins AE1/AE3, EMA, PAX8, p16, and estrogen receptors. Protein p53 showed an aberrant type of expression. Molecular genetic analysis revealed mutations in the TP53 and PIKP53CA genes. Based on our results, we believe that the tumor represents an unusual morphological variant of endometrial serous carcinoma.To the best of our knowledge, only six cases of LELC arising in endometrium have been reported in literature to date.